Pola Komunikasi Persuasif Guru dalam Membangun Motivasi Belajar Siswa dalam Studi Pendekatan Teori Komunikasi Persuasif - Salsabilla, Keisya Alifia; Fadillah, Dani (Universitas Muhammadiyah Magelang, 2025)
This study examines the persuasive communication patterns used by sixth grade teachers at SD Negeri 1 Wonosari to improve students' learning motivation. Teacher-student communication is considered crucial in creating an inspiring learning atmosphere. With a qualitative case study approach, data were collected through observation, questionnaires to 15 students, and in-depth interviews with teachers and students. This study refers to the Persuasive Communication Theory, ARCS Motivation Model, and Social Learning Theory. The results showed that teachers implemented various persuasive strategies such as verbal motivation, use of stories and analogies, emotional support, and providing space for students to ask questions. These strategies have proven effective in increasing students' self-confidence, emotional involvement, and intrinsic motivation. Teacher communication not only conveys material but also acts as a strategic tool in building learning motivation and positive self-concept. These findings provide practical contributions for educators in designing effective communication strategies, as well as theoretical contributions by filling the gap in the literature related to persuasive communication in elementary education. This study also encourages teacher training and further studies on the long-term impact of communication strategies on student development.